MALAYSIA'S TERTIARY STUDENT’S TO THE TENDENCIES INTEREST OF INTEGRITY AND THE THREAT OF CORRUPTION - Hasrul, Hashom; Nor Aisyah, Ahmad; Suharne, Ismail; Mohd Hisyamuddin, Basabah; Siti Aisyah, Edros; Mohd Fadhil, Mohd Faudzi; Musfirah, Mohamad; Mohd Hakim, Hashom (2025)
Corruption remains a significant threat to governance, social equity, and sustainable development, particularly in developing countries. In Malaysia, efforts to promote integrity and combat corruption have been central to public policy, yet the attitudes and perceptions of the younger generation—especially tertiary students—remain under explored. Under the National Anti-Corruption Plan (NACP) 2019–2023, the Malaysian government has mandated that higher education institutions introduce and implement integrity and anti-corruption courses beginning in 2023. The primary objective is to cultivate a strong sense of ethical responsibility among students, ensuring they recognize their role in upholding integrity and contributing to national efforts to combat corruption. This study investigates the relationship between the tendency toward integrity (IT) and the perceived threat of corruption (CT) among tertiary-level students in Malaysia. A total of 219 participants, primarily from higher education institutions in Malaysia, were surveyed to explore how awareness and perception of corruption influence personal integrity values. The research employed descriptive statistics, correlational analysis, and linear regression to examine the interplay between the two constructs. The findings revealed a strong and statistically significant positive correlation between perceived corruption threat and integrity tendency. Specifically, the perceived corruption threat was found to explain 62.4% of the variance in integrity tendency, suggesting that as students become more aware of corruption and its consequences, they are more likely to develop and exhibit a stronger inclination toward ethical behavior and personal integrity. These results highlight the importance of reinforcing anti-corruption education and awareness campaigns within academic settings. Cultivating integrity among students may serve as a key strategy for long-term cultural and institutional reform. The study contributes to the growing body of literature on youth integrity development and underscores the role of perceived societal threats in shaping ethical values.